Zarlino's harpsichord - Sukljan, Nejc (Muzikološki zbornik, 2018)
This paper deals with the tuning question as it is discussed in Gioseffo Zarlino's principal musical-theoretical treatise, Istitutioni harmoniche (1558). First, Zarlino's tuning system in vocal music (the syntonic diatonic) is presented; then, its shortcomings are discussed; and finally, its adjustment (temperament) for the use in instrumental music is explained.
Keywords: 16.st.; glasbena teorija; muzikologija; renesansa; uglasitev; Zarlino, Gioseffo